“Struggling with daily life and enduring pain”: a qualitative study of the experiences of pregnant women living with pelvic girdle pain - Persson, Margareta (BioMed Central, 2013)
BACKGROUND: Few studies have investigated the experiences of living with pelvic girdle pain (PGP) and its impact on pregnant women’s lives. To address this gap in knowledge, this study investigates the experiences of women living with PGP during pregnancy. METHODS: A purposive sample, of nine pregnant women with diagnosed PGP, were interviewed about their experiences. Interviews were recorded, transcribed to text and analysed using a Grounded Theory approach. RESULTS: The core category that evolved from the analysis of experiences of living with PGP in pregnancy was “struggling with daily life and enduring pain”. Three properties addressing the actions caused by PGP were identified: i) grasping the incomprehensible; ii) balancing support and dependence and iii) managing the losses. These experiences expressed by the informants constitute a basis for the consequences of PGP: iv) enduring pain; v) being a burden; vi) calculating the risks and the experiences of the informants as vii) abdicating as a mother. Finally, the informants’ experiences of the consequences regarding the current pregnancy and any potential future pregnancies is presented in viii) paying the price and reconsidering the future. A conceptual model of the actions and consequences experienced by the pregnant informants living with PGP is presented. CONCLUSIONS: PGP during pregnancy greatly affects the informant’s experiences of her pregnancy, her roles in relationships, and her social context. For informants with young children, PGP negatively affects the role of being a mother, a situation that further strains the experience. As the constant pain disturbs most aspects of the lives of the informants, improvements in the treatment of PGP is of importance as to increase the quality of life. This pregnancy-related condition is prevalent and must be considered a major public health concern during pregnancy.